Effect of Phototherapy on Total Serum Magnesium Level in Neonatal Jaundice - Thani, Kamal Prasad; Rai, Ganesh Kumar (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Neonatal jaundice is a common cause of morbidity encountered in the first week of life. Most preterm neonates develop clinical jaundice, and among term neonates, around eighty-five percent develop jaundice. Peak total bilirubin level >12.9 mg/dl is found in 6.1% of well-term newborns. Three percent of normal term infants have a total bilirubin level >15 mg/dl. Phototherapy is one of the main modalities of treatment of hyperbilirubinemia. A decrease in serum magnesium level is thought to be one of the side effects of phototherapy in neonatal jaundice. Objective: The objective of this study was to evaluate the difference in serum magnesium levels before and after phototherapy in neonates. Methods: A Descriptive study was conducted in the Neonatal Intensive Care Unit (NICU) and emergency ward of Kanti Children’s Hospital (KCH). Any neonate admitted with the diagnosis of neonatal jaundice in phototherapy and meeting inclusion criteria were included in the study. Data were analyzed using Statistical Package for Social Sciences (SPSS). Results: A Total of 54 neonates that needed phototherapy were enrolled in the study. The mean serum magnesium level before phototherapy was 2.02 ±0.25 mg/dl and it was 1.77 ±0.29 mg/dl after phototherapy. The difference was statistically significant with the p-value of <0.001 in both sexes and age groups of five days and lower. Conclusion:The mean serum magnesium level along with the mean total serum bilirubin level reduced significantly after phototherapy in neonates with hyperbilirubinemia irrespective of age, sex, and type of phototherapy.